Comprehensive analysis of the position error and vibration characteristics of Delta robot. (17th October 2016) - Zheng, Kunming; Zhang, Qiuju
Abstract: Taking Delta robot as research object, its characteristics of position error and vibration are analyzed synthetically. Using the position characteristic of driven arms, based on the method of geometry space vector, establish the mechanism error model; Taking use the principle of mathematical statistics and space vector as the basic, deriving the joint clearance error model; Based on finite element theory, on the basic of elastic dynamic model, establishing the flexible error model. Then, the kinematics and dynamics of branched chain with joint clearance generalized collision force are studied. Based on the definition of rod virtual length, combining the generalized collision force with the elastic dynamics model which includes mechanism error, joint clearance error and flexible error, establishing the comprehensive elastic dynamic model. Finally, by use of simulation software, numerical calculation and experiment, verified the correctness of comprehensive elastic dynamic model, and the characteristics of position error and vibration are analyzed. Graphical Abstract: